Kakawati (Gliricidia seplum) leaves as a mosquito repellent laundry aid a comparative study using two different extraction techniques - Lim, Josefina April C.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Repellent application on clothing is a method of personal protection against mosquitoes and Dengue fever. Due to side effects of chemicals, research has been directed towards finding organic plant alternatives. Pure plant extraction procedures could incur high costs, thus in this research a low-cost method of extraction was explored. This research experimented on kakawati (Gliricidia sepium) leaves as an anti-mosquito laundry aid by comparing kakawati extracts obtained through Soxhlet extraction and kakawati extracts obtained through decoction method. A laundry aid with 40% kakawati leaf Soxhlet extract and a laundry aid with 40% kakawati leaf decoction extract were tested and compared on poly-cotton swatches for mosquito repellent efficacy, side effects, and commercial viability. A commercial laundry aid with mosquito repellent claims, Brand X, was also tested. Bioassay results showed that the experimental kakawati infused laundry aids exhibit mosquito repellency above the passing rate. There is no significant difference between the mosquito repellent efficacy of kakawati Soxhlet extract-infused laundry aid and kakawati decoction extractinfused laundry aid. In terms of low staining side effects and high commercial viability, the decoction extract performed better than the Soxhlet extract. Although Brand X performed best in terms of side effects and commercial viability, it failed the mosquito contact bioassay test. Results suggest that the kakawati leaf decoction-extract has potential to be used as an anti-mosquito fabric treatment. However, its odor and staining properties need further improvement.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Insect baits and repellents -- Philippines; Kakawati leaves